30 years of integration in the Baltic Sea Region: security against the background of the current geopolitical situation - Śmigerska-Belczak , Iwona (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
The aim of the article is to attempt to assess the results achieved in the economic and political field from the perspective of past cooperation as well as to see whether the directions and forms of this cooperation remain adequate to the challenges expected to be faced in the near future. In the current situation, the process of sustainable development implemented, among others, through the introduction of the concept of circular economy seems to be a solution guaranteeing security in all areas as well as further development.